Occupant-centered evaluation on indoor environments and energy savings of radiant cooling systems with high-intensity solar radiation. (August 2022) - A, Yongga; Li, Nianping; He, Yingdong; Yuan, Chenzhang; Zhou, Linxuan; Lu, Jilong
Highlights: The non-uniform thermal environment under non-exposed-beam and exposed-beam solar radiation were evaluated respectively. A simplified human body model was proposed to evaluate general and local thermal comfort effected by solar radiation. Radiant cooling systems were compared with conventional air conditioning system. The energy-saving potential of radiant cooling systems was analyzed. Abstract: Solar radiation has an overwhelming influence on indoor thermal and light environments, as well as building energy consumption. In this study, radiant cooling systems were applied to reduce the negative effects of solar radiation. The tests were carried out with the floor radiant cooling system (FRC), ceiling radiant cooling system (CRC), ·and conventional air conditioning system (AC), under typical warm days. An occupant-centered body model was presented to comprehensively evaluate the non-uniform thermal environment caused by solar heat. Besides, the effects on the cooling performance of cooling systems were evaluated by simulation and experiments. The results demonstrate that the cooling capacity rapidly increased with the intensity of the solar radiation. During beam-exposed period, cooling capacity of FRC system increased from 55.6 W/m 2 to 210.0 W/m 2 and the proportion of shortwave radiant heat flux q sr reached 84%. Furthermore, solar radiation also deteriorated the non-uniform thermal environment. The FRC system could reduce the mean radiant temperature by the maximum of 8.0 °C. Exposed to the beam solar radiation was the main reason that caused large vertical stratification of temperature and dissatisfaction. The FRC system effectively performed better with the maximum percentage dissatisfied value reduced by 14.76 %. Finally, the energy-saving potential of RC systems was analyzed. After the set-point temperature was corrected, the FRC system reduced the typical day's energy consumption by 21.7% and annual energy consumption by 12.2%. Appropriate adoption of RC systems is an energy-saving method to improve thermal comfort of indoor environments with high-intensity solar radiation.